Police Recruits’ Perceptions of the Utility of Body-Worn Cameras as a Training Tool - Deck, Sarah L. (Criminal justice and behavior, 2025)
Concerns about police behavior, especially police use of force, necessitate the identification of training procedures that optimize learning outcomes for police. This study explored the potential of body-worn cameras (BWCs) as a feedback tool during police training. Police recruits (N = 111) who had experienced a simulated use of force scenario and observed their BWC footage of that event were asked open-ended questions about their experiences observing their footage. Inductive thematic analysis of their responses indicated that BWC footage encouraged recruits to be active learners, helping them self-assess their performance and enriching their capacity to engage with expert feedback. Viewing BWC footage clarified areas for improvement, contextualized feedback, and enhanced recruits’ confidence in their performance. These findings provide strong support for the potential of BWCs to enhance training outcomes and lay the groundwork for future investigations to explore the effectiveness of BWC for this purpose via controlled systematic means.